The Knowledge, Attitudes, and Practices of Community Pharmacists in their Approach to Antibiotic Use: A Nationwide Survey in Italy - Francesco Napolitano; Giorgia Della Polla; Caterina De Simone; Chiara Lambiase; Concetta Paola Pelullo; Italo Francesco Angelillo (MDPI AG, 2019)
Background: This investigation has been carried out to evaluate the knowledge, attitudes, and practices toward antibiotic resistance and antibiotic use among community pharmacists in Italy and to investigate their influencing factors. Methods: A cross-sectional telephone survey using a semi-structured interview was performed between September 2018 and April 2019 among a random sample of community pharmacists. Results: Almost two thirds (61.5%) correctly answered that the overuse of antibiotics in primary care, hospital settings, and veterinary medicine is a significant cause of antibiotic resistance. Males, those who worked a lower number of hours per week, and those who acquired information through scientific journals and educational activity were more likely to know that the overuse of antibiotics causes antibiotic resistance. More than two thirds of those pharmacists (70.8%) often or always inform the public about the risks of antibiotic resistance. Those who have been practicing for a higher number of years were more likely to act in that way, whereas pharmacy directors and those who did not need additional information on antibiotic resistance were less likely to inform the public. Conclusions: Pharmacists need to be aware of the issue of antibiotic resistance and policy makers should promote the implementation of antibiotic use public educational interventions in this setting.